TEORI TATA BAHASA UNIVERSAL - Soepomo Peodjosoedarmo (Universitas Muhammadiyah Surakarta, 2005)
The main aim of this writing is to formulate the theory of universal grammar. The formulation made is taken form discussion on a close look at the universal grammar which of summary proposed by Greenberg and Hawkins. The items being searched are not about elements such as subject, predicate, object respectively in sentence, but the categories of words for example (N) (V) in forming a simple sentence.the result of discussing universal grammar shows that (1) Chomsky's model universal grammar; (2) Greenberg's model of universal grammar devides languages in the world into three types of universal world order (universal phrase sequence) = Verb + Subject + Object (VSO), Subject + Verb + Object (SVO), and Subject + Object + Verb (SOV); (3) Hawkins's model of universal grammar states that based on word order, language the world can be formulated into 24 types. Moreover, such types consist of groups of subtype and category V, S and O which are usually used to classify the types based on proposition and postposition, (4) the continued universal grammar states a different coocurence sequence, which reveals comparison-base which is not S, V, O, but category such as S, V, N, N. The first N is subject, the second one is indirect object, and the third N is direct object. In this case it is clear that S or O is represented by N; (5) when there is sequence NNN uninserted by V, a mark is needed to show which N as subject, device or indirect object. The mark can be seen as in rowd order N before V is subject, or N after V indirect object, while the second after V is direct object. If the states of N-N changes, there must be a certain postverb (postposition) to indicate the indirect object; (6) the adposition of language with a pattern VSO or SVO is preposition, while in the language SOV, the adposition is postposition.Key words: universal grammar, tipology, natural languages, and word order.